2012
DOI: 10.1002/art.34451
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles for complement in glomerulonephritis and atherosclerosis revealed in mice with a combination of lupus and hyperlipidemia

Abstract: Objective Although the accelerating effect of systemic lupus erythematosus (SLE) on atherosclerosis is well established, the underlying mechanisms are unknown. The aim of this study was to explore the hypothesis that lupus autoimmunity modulates the effect of hypercholesterolemia in driving arterial pathologic development.>Methods Low-density lipoprotein receptor–deficient (Ldlr−/−) mice were crossed with B6.129-Sle16 (Sle16)–congenic autoimmune mice to obtain Sle16. Ldlr−/− mice, which were compared with Ldlr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 48 publications
3
11
0
Order By: Relevance
“…Anti-OSE antibodies in WT mice are primarily produced by B1 cells, but adaptive B2 cell clones with similar specificity are induced by 51 and based on the presence of class-switched IgG antibodies, also expand and become plasma cells in atherosclerotic mice. 52 In our study, antibodies against OSE were significantly reduced in a similar way to total antibody levels by both XBP1 deficiency and anti-CD4 depletion. Previously, MDA-LDL immunization induced a prominent Th2-type CD4 + T cell response and an IL-5 dependent increase in antioxLDL IgM production, 11 which in vitro was solely produced in response to IL-5 by B1a cells.…”
Section: 44supporting
confidence: 74%
“…Anti-OSE antibodies in WT mice are primarily produced by B1 cells, but adaptive B2 cell clones with similar specificity are induced by 51 and based on the presence of class-switched IgG antibodies, also expand and become plasma cells in atherosclerotic mice. 52 In our study, antibodies against OSE were significantly reduced in a similar way to total antibody levels by both XBP1 deficiency and anti-CD4 depletion. Previously, MDA-LDL immunization induced a prominent Th2-type CD4 + T cell response and an IL-5 dependent increase in antioxLDL IgM production, 11 which in vitro was solely produced in response to IL-5 by B1a cells.…”
Section: 44supporting
confidence: 74%
“…Previous literature concluded that hyperlipidemia will enhance renal immune complex-mediated complement activation and development of nephritis, in the current study, hyperlipidemia was positively correlated with proteinuria and lupus nephritis confirming the aforementioned observation [18]. In the present study, a correlation was found between hypocomplementemia and dyslipidemia that can be explained by the small size of our study.…”
Section: Discussionsupporting
confidence: 90%
“…Increasing evidences indicated that the complement system could be activated within atherosclerotic plaques[ 31 ]. Recently, Lewis et al found that, in a mice model combining with lupus and hyperlipidemia, accelerated arteriosclerosis of aorta was related to complement activation and reduced uptake and removal of apoptotic/necrotic debris[ 32 ].…”
Section: Discussionmentioning
confidence: 99%